Hoje é dia de Maria , da criança e do diabo: construções identitárias - Conti, Maria Aparecida (2013)
In this research, we aim to explain the discursive construction process of devil and child identities throughout analyses of the discourse which crosses the miniseries Hoje é dia de Maria. Specifically, we are interested in the discursive process used to maintenance/deconstruction of knowledge about the identity constituents which involve the child and devil in our society. Hence, in order to support the effects of meaning that emerge from the text, pointing to aspects socioculturally produced in-between places of childhood and devil memory, we mobilized a theoretical interface with Discourse Analyses (with emphasis on Foucault s theory), socio-cultural and philosophical studies. Whereas, in our society, the supposed effect of unity produced by these discursive subject seems warranted by a function-subject that is favorable to the maintenance of metaphysical myth of human duality (which works with the dichotomies: body x soul; unreal x real, beautiful x ugly, good x bad etc..) we assume that such way of thinking contributes to the discursive constitution of human identities aimed at maintaining ethical and moral principles grounded in Christian religious belief. Our analysis points to the deconstruction of the myth established in our society. This finding is based on the fact that the statement that allows the crossing of different sayings can reiterate the character of fluidity of the identities, as pointed out by Bauman, Hall and others. Considering this, we recognize that the concept of representation appears to be quite profitable, once it is an integrant part of the discursive work by which the meaning is produced. This productivity appeared in the discursive thread from the interplay of forces between legible and illegible constitutive of crossings of a linguistics dimension constituted by verbal linguistic signs (jargon, dialectal expressions, etc.) and nonverbal (pictures, sounds, colors, etc.). Thus, based on the discursive functioning of the miniseries, the (re)construction of representations about the child and about the devil contributed to the (de)stabilizing characteristics socially disseminated. In other words, we could analyze how the truths about the child and the devil were built in our society and that these representations were, in our view, deconstructed. Maybe because it is literary, the movie script of the miniseries Hoje é dia de Maria can bring the devil and the child as discursive subject functioning as the concept devir-child and allows that art, especially literature, continues to cause surprise and delight, mainly by enable those who read/watch to reinvent themselves once the speeches are coming from an exterior that constitute the discursive subject and, therefore, individuals who assume the various positions in which subjects are constituted socio-historically and comes out through the language.